PEMUPUKAN NPK LODRIN 20-14-13 PRODUKSI CV SCORLEST PADA PEMBIBITAN KOPI (Coffea,sp) UNTUK MENGETAHUI TINGKAT EFISIENSI - M. Saeri; F. N. Aziz (JOURNAL SOCIO ECONOMICS AGRICULTURAL, 2018)
The importance of NPK fertilizer for plants makes testing NPK fertilizer important to know the quality of fertilizer sold in the market. CV. Scorlest produces NPK fertilizers with doses of 20-14- 13 and labeled Lodrin. This fertilizer also needs to be tested its effectiveness on the resulting coffee seedlings. The use of NPK fertilizer is expected to affect the index of the readiness of seeds in coffee plants. Based on this research, this study aims to determine the level of effectiveness and efficiency of Lodrin fertilizer 20-14-13 on the growth of coffee seedlings. This experiment was conducted in the village of Kemiri, Jabung District, Malang Regency, conducted from August 2016 until December 2016. The experiment used a complete randomized block design with three replications. The clones used are BP 308 age 7 months. Based on the results of experiments conducted Lodrin Fertilizer 20-14-13 have the best quality seed index at a minimum dose of 3.5g per plant plus 0.75g urea per plant technically this fertilizer passed as equal to standard fertilization and higher than the control. Lodrin fertilizer 20-14-13 gives R / C ratio of 3.14 so that economically fertilizer is feasible for use in coffee cultivation business.